2010
DOI: 10.1002/jssc.201000212
|View full text |Cite
|
Sign up to set email alerts
|

Efficient isolation and purification of five products from microbial biotransformation of cinobufagin by high‐speed counter‐current chromatography

Abstract: An efficient separation method of using high-speed counter-current chromatography was successfully established to directly purify cytotoxic transformed products of cinobufagin by Cordyceps militaris. The two-phase solvent system composed of n-hexane-ethyl acetate-methanol-water (4:6:3:4, v/v) was used in high-speed counter-current chromatography. A total of 9 mg of 4beta,12alpha-dihydroxyl-cinobufagin (1), 15 mg of 12beta-hydroxyl-cinobufagin (2), 8 mg of 5beta-hydroxyl-cinobufagin (3), 12 mg of deacetylcinobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Five bufadienolides were isolated from the microbial biotransformation of cinobufagin by Ma et al, utilizing a solvent system consisting of nhexane, ethyl acetate, methanol, and water (Wat) (4:6:3:4, v/v). The purity of these compounds exceeded 90% [17]. Li et al developed a stepwise elution method using a two-phase solvent system consisting of n-hexane/ethyl acetate/methanol/Wat at the ratios of 4:6:2:4 (v/v), 4:6:2.5:4 (v/v), and 4:6:3.2:4 (v/v) for the purification of bufadienolides from ChanSu by CCC.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Five bufadienolides were isolated from the microbial biotransformation of cinobufagin by Ma et al, utilizing a solvent system consisting of nhexane, ethyl acetate, methanol, and water (Wat) (4:6:3:4, v/v). The purity of these compounds exceeded 90% [17]. Li et al developed a stepwise elution method using a two-phase solvent system consisting of n-hexane/ethyl acetate/methanol/Wat at the ratios of 4:6:2:4 (v/v), 4:6:2.5:4 (v/v), and 4:6:3.2:4 (v/v) for the purification of bufadienolides from ChanSu by CCC.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, the utilization of CCC also exhibits economic advantages and facilitates high product purity [14,15]. Furthermore, the successful separation of bufadienolides from ChanSu was achieved through a one-step CCC [16][17][18]. Five bufadienolides were isolated from the microbial biotransformation of cinobufagin by Ma et al, utilizing a solvent system consisting of nhexane, ethyl acetate, methanol, and water (Wat) (4:6:3:4, v/v).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some studies have revealed that natural products which exist in the traditional Chinese medicines [ 26 ], have the potential properties in treating different types of cancers. Toad venom (called “ Chansu ” in China) is a product of the skin gland of toads such as Bufo bufo gargarizans etc [ 27 , 28 ], which has been widely used as a cardiotonic, diuretic, anodyne and hemostatic agent [ 29 ]. Chansu has been used as significant anticancer agents, amending the life quality of cancer patients [ 30 ].…”
Section: Introductionmentioning
confidence: 99%